Effectiveness of Lee Silverman Voice Treatment® LOUD on Japanese-Speaking Patients with Parkinson's Disease. (24th January 2020) - Nakayama, Keigo; Yamamoto, Toshiyuki; Oda, Chihiro; Sato, Masako; Murakami, Takeshi; Horiguchi, Satoshi
Abstract : Background. Lee Silverman Voice Treatment® LOUD (LSVT®) is an intensive program devised in the United States to train patients with Parkinson's disease (PD) to speak louder, at normal intensity, while keeping a good voice quality. Four weeks of LSVT® has been shown to increase vocal loudness and improve intelligibility among Japanese-speaking PD patients. However, the long-term effects of LSVT® have not been examined in these patients. Objective . This study aimed to investigate the long-term effects of LSVT® on Japanese-speaking PD patients. Methods . Twenty-one Japanese PD patients underwent a standardized course (four sessions over four consecutive days, for four weeks) of LSVT® at our hospital. Vocal loudness and intelligibility were assessed at the following three time-points: pretreatment (baseline), immediately after treatment, and at the end of the 12 month follow-up (12FU). Sound pressure levels (dB SPL) were measured during the following tasks: sustained phonation of /a/, reading a standardized text, and delivery of a monologue. Three experienced speech-language pathologists, who were blinded to patients' identities and assessment points, assessed speech intelligibility based on recorded audio samples of each participant during the reading and monologue tasks. Results . Fourteen patients were evaluated at 12FU. Changes in dB SPL from baseline to immediately after treatment were +6.5 dB, +4.2 dB, and +2.8 dB, and those from baseline until 12FU were +4.7 dB, +3.5 dB, and +2.5 dB in sustained phonation of /a/, reading a passage, and delivery of a monologue, respectively. These changes were significant ( p < 0.025) in both the baseline-to-immediately-after-treatment and baseline-to-12FU intervals. Intelligibility relative to baseline was significantly improved immediately after treatment, but not at 12FU. Conclusions . LSVT® had a long-term effect on the vocal loudness of Japanese-speaking PD patients. A short-term effect was seen in intelligibility, however, there was no significant long-term effect.